2021
DOI: 10.1002/jat.4132
|View full text |Cite
|
Sign up to set email alerts
|

Length difference of multi‐walled carbon nanotubes generates differential cytotoxic responses

Abstract: Carbon nanotubes have recently been rated as an effective biomaterial owing to their functionalization ability. However, the safety of multi‐walled carbon nanotubes (MWCNTs) has yet to be clearly understood. To investigate how cells differentially react to minor geometric differences, we prepared well‐dispersed and stable long and short MWCNTs showing an approximately 100‐nm length difference in an in vitro system. Through an optimal combination of bovine serum albumin (BSA) and fetal bovine serum (FBS) biosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Aspect ratio of asbestos fibers turned out to be one of the reasons for increased cancerogenicity [204]. Length variations in CNTs point in the same direction [205]. A provoking discussion on this issue is reported by Fadeel et al [70], which definitely reinforces the need for biomedical safety assessments of especially carbon nanomaterials in parallel to advancing the fabrication methodologies.…”
Section: Potential Cytotoxicity Of Some Carbon Nanomaterialsmentioning
confidence: 94%
“…Aspect ratio of asbestos fibers turned out to be one of the reasons for increased cancerogenicity [204]. Length variations in CNTs point in the same direction [205]. A provoking discussion on this issue is reported by Fadeel et al [70], which definitely reinforces the need for biomedical safety assessments of especially carbon nanomaterials in parallel to advancing the fabrication methodologies.…”
Section: Potential Cytotoxicity Of Some Carbon Nanomaterialsmentioning
confidence: 94%
“…Do et al found that the internalization of MWCNTs led to the cytotoxicity and mitochondrial dysfunction in human coronary artery smooth muscle cells. Smaller MWCNTs were more cytotoxic compared with larger MWCNTs, indicating a role of physicochemical properties of MWCNTs (Do et al, 2021). Similarly, our group also showed composition‐dependent cytotoxicity of NPs to human aortic smooth muscle cells, that only ZnO NPs but not TiO 2 or Ag NPs induced cytotoxicity.…”
Section: Adverse Vascular Effects Of Nmsmentioning
confidence: 99%
“…Indeed, most of the studies used VSMCs as an in vitro model to investigate the cytotoxic potential of NMs, such as calcifying NMs, 33 metal-based NMs 34,35 and CNTs. 36,37 Regarding graphene oxide, two recent studies reported that they exhibited relatively high biocompatibility in VSMCs and thus were suitable for biomedical purposes. 38,39 However, besides acting as the cells constructing the walls of blood vessels, VSMCs have also been revealed as pivotal cells involved in the regulation of pathophysiology of blood vessels as endothelial cells.…”
Section: Introductionmentioning
confidence: 99%